2019
DOI: 10.3906/elk-1810-10
|View full text |Cite
|
Sign up to set email alerts
|

A robust SMES control for enhancing stability of distribution systems fed from intermittent wind power generation

Abstract: The voltage and frequency stability issues of power systems are the main challenges that arise from high penetration levels of wind energy systems. This paper presents an effective solution for voltage and frequency stability problems by using a superconducting magnetic energy storage (SMES) system controlled with a fuzzy logic controller (FLC). The proposed control system can suppress the voltage and frequency fluctuations due to the high variations of wind speed. In addition, the proposed control system is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…For example, financial subsidies and favorable tax policies should be considered carefully to improve the applied proportion of clean energy. Based on the development status, many researchers have performed related studies involving solar power [82,83], hydropower [84,85], and wind power [86,87].…”
Section: Improving the Proportion Of Renewable Energy Usementioning
confidence: 99%
“…For example, financial subsidies and favorable tax policies should be considered carefully to improve the applied proportion of clean energy. Based on the development status, many researchers have performed related studies involving solar power [82,83], hydropower [84,85], and wind power [86,87].…”
Section: Improving the Proportion Of Renewable Energy Usementioning
confidence: 99%
“…The transient stability improvement using SMES in the presence of DFIG is presented in ref. 27. The impact of SMES in wind genertion system regulating point of common coupling (PCC) voltage and power during strong wind gusts are studied in ref.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research studies have shown the positive impact of SMES in RES-integrated systems. The transient stability improvement using SMES in the presence of DFIG is presented in [17,18]. The impact of SMES in WGS regulating PCC voltage and power during strong wind gusts is studied in [19].…”
Section: Introductionmentioning
confidence: 99%